Tunable broadband photoluminescence from bismuth‐doped calcium aluminum germanate glasses prepared in oxidizing atmosphere. Issue 9 (6th May 2022) - Cao, Jiangkun; Ding, Yicong; Limbach, René; Nozari, Vahid; Sajzew, Roman; Sun, Minghui; Zhang, Pengzhu; Wondraczek, Lothar
Abstract: Tunable photoluminescence (PL) from transparent inorganic glass matrices is of interest for applications demanding a semitransparent photoconverter that does not elastically scatter incoming light. For this purpose, bismuth (Bi)‐doped optical materials exhibit unique spectral characteristics in terms of bandwidth and emission tunability. Here, we demonstrate a facile route for preparing such converters from Bi‐doped calcium‐aluminate and calcium‐aluminogermanate glasses. These glasses offer tunable PL across the near violet and visible‐to‐near‐infrared (NIR) spectral range, with an emission lifetime in the range of 300 μs. The addition of GeO2 exerts a decrease in optical basicity, which in turn enables the stabilization of NIR‐active low‐valence Bi species for broadband NIR PL.